The effect of red grape seed extract on serum paraoxonase activity in patients with mild to moderate hyperlipidemia - Argani, Hassan; Ghorbanihaghjo, Amir; Vatankhahan, Hamid; Rashtchizadeh, Nadereh; Raeisi, Sina; Ilghami, Hadi (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Red grape seed extract (RGSE) contains oligomeric proanthocyanidin complexes as a class of flavonoids. These compounds are potent antioxidants and exert many health-promoting effects. This study aimed to determine the effects of RGSE on serum levels of triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), apolipoprotein AI (apo-AI) levels and paraoxonase (PON) activity in patients with mild to moderate hyperlipidemia (MMH). DESIGN AND SETTINGS: A randomized double-blind placebo-controlled clinical trial was conducted at Shahid-Modarres Hospital (Tehran, Iran) and Tabriz University of Medical Sciences. Seventy MMH patients were randomly assigned to receive treatment (200 mg/day of RGSE) or placebo for eight weeks. RESULTS: Significant elevation in serum levels of apo-AI (P = 0.001), HDL-C (P = 0.001) and PON activity (P = 0.001) and marked decreases in concentrations of TC (P = 0.015), TG (P = 0.011) and LDL-C (P = 0.014) were found in the cases. PON activity was significantly correlated with apo-AI (r = 0.270; P < 0.01) and HDL-C (r = 0.45; P < 0.001). Significant differences between the RGSE and control groups (before and after treatment) for TC (P = 0.001), TG (P = 0.001), PON (P = 0.03), apo-AI (P = 0.001) and LDL-C (P = 0.002) were seen. CONCLUSION: It is possible that RGSE increases PON activity mostly through increasing HDL-C and apoAI levels in MMH patients. It may thus have potential beneficial effects in preventing oxidative stress and atherosclerosis in these patients.